Análisis de las estrategias de la asociación ecuatoriana de ecoturismo (ASEC) para gestionar el desarrollo sostenible. - Maza Jadan, Leonardo Andres (My University, 2021)
This project is developed through the investigation and identification of strategies to publicize the different directions in which the social and environmental actors belonging to the Ecuadorian Ecotourism Association (ASEC) were found. The analysis for the good management of sustainable development was carried out through the strategies proposed, obtaining the investigation in more detail. This study shows a literature review methodology, analyzing the strategies of the Ecuadorian Ecotourism Association (ASEC) and its difficulty in positioning itself at the national level, said association is composed of two apartments that are the social actor, and environmental conservation, which is carried out throughout this research to establish long-term sustainable development. This analysis allows us to know the main strategies of ASEC focusing on managing non-profit sustainable development, sowing harmony between tourism, tourists and environmental conservation. Through the results, the point of failure for the association is interpreted, displaying some recommendations that benefit its current position at the national level.
La presente proyecto se elabora mediante la investigación e identificación de estrategias para dar a conocer las distintas direcciones en la que se encontraba los actores sociales y ambientales pertenecientes a la Asociación Ecuatoriana de Ecoturismo (ASEC). Se realizó el análisis para la buena gestión del desarrollo sostenible mediante las estrategias planteadas obteniendo de manera más detallada la investigación. Este estudio muestra una metodología de revisión bibliográfica, analizando las estrategias de la Asociación Ecuatoriana De Ecoturismo (ASEC) y su dificultad de posicionarse a nivel nacional, dicha asociación esta compuestas por dos apartamentos que son el actor social, y conservación ambiental, que se realiza a lo largo de esta investigación para establecer un desarrollo sostenible a largo plazo. Este análisis nos permite conocer las estrategias principales de ASEC enfocándose en gestionar el desarrollo sostenible sin fines de lucro, sembrando armonía entre el turismo, turistas y conservación ambiental. Mediante los resultados, se interpretó cual fue el punto de fracaso para la asociación, desplegando algunas recomendaciones que beneficien su posición actual a nivel nacional.
Keywords: DESARROLLO SOSTENIBLE; ECOTURISMO; ANÁLISIS DE ESTRATEGIAS; ASEC